THE EMERGENCY CONDITIONS IN A LOADED HALF-WAVE LINE - Rimsky V.X.; Berzan V.P.; Patsiuk V.I. (Problems of the Regional Energetics)
The emergency and postemergency states in the unloaded and loaded half-wave line without optional connections are investigated. It is found that the overvoltage ratio during the transition process induced by a short circuit (with the action time equal to 130 mc) or by a break in the circuit (with the action time equal to 60 mc) runs up to 6.